Questioner from the Bloc of Enemies? On dialogues with the expelled and displaced Germans that are led by the questioners born in Czechoslovakia (Theatrum historiae, 2014)
It is a specific situation, when a Czech researcher interviews Sudeten German expellees. On the purely symbolic level, we can say „the representative of the expulsion“ meets the expellees who were displaced 1945 from Czechoslovakia. The author of the article presents its own (not yet finished) dissertation research. She deals with the Germans from Nová Bystřice and Jindřichův Hradec and their integration in Baden-Württemberg (Germany), from a historical anthropology point of view. The author compares own experiences with the oral history interviews with the experience of the ethnologist Libuše Volbrachtová who made also interviews with Sudeten German expellees, but already in the 1980s.
Keywords: oral history; interview; Sudeten Germans; expulsion